Pushing the boundaries of radiotherapy-immunotherapy combinations: highlights from the 7th immunorad conference - Pierre-Antoine Laurent; Fabrice André; Alexandre Bobard; Desiree Deandreis; Sandra Demaria; Stephane Depil; Stefan B. Eichmüller; Cristian Fernandez-Palomo; Floris Foijer; Lorenzo Galluzzi; Jérôme Galon; Matthias Guckenberger; et al. (OncoImmunology, 2025)
Over the last decade, the annual Immunorad Conference, held under the joint auspicies of Gustave Roussy (Villejuif, France) and the Weill Cornell Medical College (New-York, USA) has aimed at exploring the latest advancements in the fields of tumor immunology and radiotherapy-immunotherapy combinations for the treatment of cancer. Gathering medical oncologists, radiation oncologists, physicians and researchers with esteemed expertise in these fields, the Immunorad Conference bridges the gap between preclinical outcomes and clinical opportunities. Thus, it paves a promising way toward optimizing radiotherapy-immunotherapy combinations and, from a broader perspective, improving therapeutic strategies for patients with cancer. Herein, we report on the topics developed by key-opinion leaders during the 7th Immunorad Conference held in Paris-Les Cordeliers (France) from September 27th to 29th 2023, and set the stage for the 8th edition of Immunorad which will be held at Weill Cornell Medical College (New-York, USA) in October 2024.